Aplicación de la simulación monte Carlo en la proyección de demanda eléctrica en un transformador de distribución. - Yanchatipan Moposita, Bryan Ivan (2023)
To carry out electrical projects, it is important to prepare a projection of electrical demand, since if it is not carried out properly, demand can be overestimated. In this project, the application of Monte Carlo simulation was carried out in the projection of electrical demand in a distribution transformer. First, a state of the art regarding Monte Carlo simulation was made. Then the chargeability parameters were determined, through measurements and surveys, which were applied to the personnel in charge of the laboratories of the CIYA faculty. The information on the number of equipment and their characteristics was collected, a classification of loads by groups was developed according to common characteristics, and the amount of utility of each one of the equipment in a normal day was established.